UNDERSTANDING NORMS AND CHANGING THEM. Issue 1 (4th December 2018) - Muldoon, Ryan
Abstract: It is crucial for policymakers to focus their attention on social norms if they want to improve policy outcomes, but doing so brings in new normative questions about the appropriate role of the state. Indeed, I argue that efforts to reduce coercion at the state level can create potentially pernicious and difficult to eliminate forms of coercion at the informal level. This creates a new normative challenge for thinking about the broader regulatory apparatus, and complicates our approach in utilizing social norms for democratic policy ends. I will distinguish between two forms of social norms orientations in policy: a diagnostic approach and a design approach. We will see that the diagnostic approach better models a Humean approach to supporting social norms, and a design approach has a more Millian character. While it is easier to justify a design approach in the abstract, as it has very little room for abuses of state authority, if Mill is right that social norms can be a source of coercive power that runs afoul of the harm principle, then a design approach will sometimes be necessary to counter this form of tyranny. However, this latter approach is complex, and as such we may want to take a recommendation from Mockus to focus on deliberative approaches to norm change.